Women’s Voices in Cyberspace: A Feminist Reading of Digital Narratives on Wattpad - Afni Rosalina; Saiful Anwar Matondang; M. Manugeren (Edulitics (Education, Literature, and Linguistics) Journal, 2025)
In the digital era, online platforms have transformed the way literature is produced and consumed, providing new spaces for marginalized voices to emerge. This study explores how women articulate their voices, identities, and lived experiences through digital literary works on Wattpad. Anchored in the framework of feminist literary criticism, the research analyzes the representation of female characters, dominant narrative themes, and stylistic patterns employed by women authors. Using a qualitative-descriptive method, several popular Wattpad stories written by female writers were examined to uncover how digital narratives reflect feminist consciousness. The findings reveal that Wattpad functions not only as a site of popular entertainment but also as a medium of emancipation and symbolic resistance against patriarchal structures. Female protagonists are often portrayed as independent, self-aware, and empowered figures who challenge traditional gender norms. Aesthetically, the narratives exhibit the characteristics of ecriture féminine, a writing style that emphasizes emotional depth, intuition, and embodiment. The study concludes that women’s digital literature on Wattpad represents a dynamic form of contemporary feminist expression, where new media act as platforms for self-articulation, solidarity, and gender awareness. This demonstrates that digital culture plays a vital role in reshaping the boundaries of literary production and in amplifying women’s voices in the modern literary landscape.